The Incidences Of Kidnapping In An Urban Sprawl: Insights From White Sand, Lagos State, Nigeria. - Attoh, Franca Chitoh; Fapetu, Emmanuel (Advances in Social Sciences Research Journal, 2018)
The focus of this study is the various incidences of kidnapping in one of the urban sprawls called White Sand in Ikotun/Igando in Alimosho Local Government, Lagos State, Nigeria. This is a qualitative study which involved indepth interviews with fifteen residents from the study location. The study hinged on Anomie theory and the Broken Window theory. The theoretical presupposition of the study is that given the prevalence of crime occasioned by the unequal access to legitimate opportunity in the society, urban sprawls without the presence of security apparatus are highly vulnerable to the invasion of criminals and in particular, kidnappers. The findings of the study revealed that absence of state security, unchecked incidence of minor crimes and the availability of easy route of escape were responsible for the invasion of the study location by kidnappers. The study also shows that anyone can be a victim of kidnapping and that collective effort by the community and security agents has the potency of stemming the tide of crime. The study therefore recommended that the government should ensure that police posts are established in all existing sprawls in the state and that the state’s neighbourhood watch should be extended to the sprawls in order to protect them from criminal onslaughts.